Seasonal storage and alternative carriers: A flexible hydrogen supply chain model. (15th August 2017) - Reuß, M.; Grube, T.; Robinius, M.; Preuster, P.; Wasserscheid, P.; Stolten, D.
Highlights: Techno-economic model of future hydrogen supply chains. Implementation of liquid organic hydrogen carriers into a hydrogen mobility analysis. Consideration of large-scale seasonal storage for fluctuating renewable hydrogen production. Implementation of different technologies for hydrogen storage and transportation. Abstract: A viable hydrogen infrastructure is one of the main challenges for fuel cells in mobile applications. Several studies have investigated the most cost-efficient hydrogen supply chain structure, with a focus on hydrogen transportation. However, supply chain models based on hydrogen produced by electrolysis require additional seasonal hydrogen storage capacity to close the gap between fluctuation in renewable generation from surplus electricity and fuelling station demand. To address this issue, we developed a model that draws on and extends approaches in the literature with respect to long-term storage. Thus, we analyse Liquid Organic Hydrogen Carriers (LOHC) and show their potential impact on future hydrogen mobility. We demonstrate that LOHC-based pathways are highly promising especially for smaller-scale hydrogen demand and if storage in salt caverns remains uncompetitive, but emit more greenhouse gases (GHG) than other gaseous or hydrogen ones. Liquid hydrogen as a seasonal storage medium offers no advantage compared to LOHC or cavern storage since lower electricity prices for flexible operation cannot balance the investment costs of liquefaction plants. A well-to-wheel analysis indicates that all investigated pathways have less than 30% GHG-emissions compared to conventional fossil fuel pathways within a European framework.